Größe, Anlageformen, Befestigungsarchitektur und Innenflächenbebauung der frühen slawischen Burgen im südlichen Hinterland der Ostsee - Kieseler, Andreas (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2019)
Owing to dendrochronological data and archaeological finds, more than 150 strongholds from the southern coastal area of the Baltic Sea between the Lower Elbe and the Lower Vistula, can be identified as the oldest large-scale “fortification horizon” in the North-Western Slavic territories. They developed as early as in the 8th and 9th centuries. Generally, the strongholds are regarded seats of tribal elites. Owing to the rapid development of the local economy and contacts with the neighbouring cultural zones, particularly the Frankish Empire and Scandinavia (ports of trade), the strongholds evolved relatively early in the North-Western Slavic territories. This article focuses on the different aspects of the strongholds’ operations: spreading, location, layout, size, construction types, and building structures, in order to present in detail the architectural specifics of the imposing, strongly fortified ramparts. On the basis of archaeological research, the author highlights the erection of the sector fortifications and the joining palisade-like constructions, along with a variety of construction types and materials used. The regional differences in size and the historical-cultural background of these strongholds are also discussed.